Cauda equina neuroendocrine tumors show biological features distinct from other paragangliomas and visceral neuroendocrine tumors - Soukup, Jiri; Manethova, Monika; Kohout, Ales; Soukup, Tomas; Dvorakova, Radka; Drugda, Jan; Vitovcova, Barbora; Gabalec, Filip; Kaiser, Miroslav; Kanta, Martin; Kasparova, Petra; Kozak, Jan; et al. (Virchows Archiv, 2023)
Cauda equina neuroendocrine tumors (CENETs) are neoplasms of uncertain histogenesis with overlapping features between those of paragangliomas (PGs) and visceral neuroendocrine tumors (NETs). We have explored their biological relationship to both subsets of neuroendocrine neoplasms. The clinical and radiological features of a cohort of 23 CENETs were analyzed. A total of 21 cases were included in tissue microarrays, along with a control group of 38 PGs and 83 NETs. An extensive panel of antibodies was used to assess epithelial phenotype (cytokeratins, E-cadherin, EpCAM, Claudin-4, EMA, CD138), neuronal and neuroendocrine features (synaptophysin, chromogranin A, INSM1, neurofilaments, NeuN, internexin-α, calretinin), chromaffin differentiation (GATA3, Phox2b, tyrosine hydroxylase), and possible histogenesis (Sox2, T-brachyury, Oct3/4, Sox10). The cohort included 5 women (22%) and 18 men (78%). The average age at the time of surgery was 48.3 years (range from 21 to 80 years). The average diameter of the tumors was 39.27 mm, and invasion of surrounding structures was observed in 6/21 (29%) tumors. Follow-up was available in 16 patients (median 46.5 months). One tumor recurred after 19 months. No metastatic behavior and no endocrine activity were observed. Compared to control groups, CENETs lacked expression of epithelial adhesion molecules (EpCAM, CD138, E-cadherin, Claudin-4), and at the same time, they lacked features of chromaffin differentiation (GATA3, Phox2b, tyrosine hydroxylase). We observed no loss of SDHB. Cytokeratin expression was present in all CENETs. All the CENETs showed variable cytoplasmic expression of T-brachyury and limited nuclear expression of Sox2. These findings support the unique nature of the neoplasm with respect to NETs and PGs.
Keywords: Paragangliomas; Humans; paragangliom; neuroendokrinní nádory; Cauda Equina; Transcription Factors; Female; claudin-4; Claudin-4; lidé; Neuroendocrine Tumors; Immunohistochemistry; represorové proteiny; Cauda equina; nádory centrálního nervového systému; tyrosin-3-monooxygenasa; Paraganglioma; Sox2; Central Nervous System Neoplasms; Repressor Proteins; ženské pohlaví; Tyrosine 3-Monooxygenase; Neuroendocrine tumors; adhezní molekula epiteliálních buněk; Epithelial Cell Adhesion Molecule; cauda equina; transkripční faktory; lokální recidiva nádoru; Neoplasm Recurrence, Local